2017
DOI: 10.1038/s41467-017-00212-4
|View full text |Cite
|
Sign up to set email alerts
|

The non-coding RNA landscape of human hematopoiesis and leukemia

Abstract: Non-coding RNAs have emerged as crucial regulators of gene expression and cell fate decisions. However, their expression patterns and regulatory functions during normal and malignant human hematopoiesis are incompletely understood. Here we present a comprehensive resource defining the non-coding RNA landscape of the human hematopoietic system. Based on highly specific non-coding RNA expression portraits per blood cell population, we identify unique fingerprint non-coding RNAs—such as LINC00173 in granulocytes—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
171
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(176 citation statements)
references
References 69 publications
(128 reference statements)
5
171
0
Order By: Relevance
“…[248][249][250] Several bioinformatic studies have inferred roles for miRNAs in regulatory networks, 251 Long noncoding RNAs (lncRNAs, >200 bp) are emerging as key regulators of a growing number of normal biological process including cell differentiation and identity 253 and are differentially expressed in myelodysplastic syndrome and AML. [254][255][256][257] Recent studies have shown that lncRNAs are required for normal hematopoiesis where they regulate HSC activity and function, as well as myeloid and lymphoid differentiation. 256,258 Expression is cell type specific in human hematopoiesis, 256 and the expression of just four lncRNAs is sufficient to predict patient outcome across multiple AML cohorts.…”
Section: Noncoding Rnas An Emerging Path To Transcriptional Dysregmentioning
confidence: 99%
See 1 more Smart Citation
“…[248][249][250] Several bioinformatic studies have inferred roles for miRNAs in regulatory networks, 251 Long noncoding RNAs (lncRNAs, >200 bp) are emerging as key regulators of a growing number of normal biological process including cell differentiation and identity 253 and are differentially expressed in myelodysplastic syndrome and AML. [254][255][256][257] Recent studies have shown that lncRNAs are required for normal hematopoiesis where they regulate HSC activity and function, as well as myeloid and lymphoid differentiation. 256,258 Expression is cell type specific in human hematopoiesis, 256 and the expression of just four lncRNAs is sufficient to predict patient outcome across multiple AML cohorts.…”
Section: Noncoding Rnas An Emerging Path To Transcriptional Dysregmentioning
confidence: 99%
“…[254][255][256][257] Recent studies have shown that lncRNAs are required for normal hematopoiesis where they regulate HSC activity and function, as well as myeloid and lymphoid differentiation. 256,258 Expression is cell type specific in human hematopoiesis, 256 and the expression of just four lncRNAs is sufficient to predict patient outcome across multiple AML cohorts. 255 Some lncRNAs, including those that originate from leukemia-associated genomic regions, function as oncogenic drivers in acute leukemia.…”
Section: Noncoding Rnas An Emerging Path To Transcriptional Dysregmentioning
confidence: 99%
“…Hence, disruption of cellular processes in particular cell types may lead to phenotypic alterations or development of disease. This presumption in conjunction with the complexity of tissue-level (“bulk”) data has led to many cell-type-specific genomic studies, in which genomic features, such as gene expression levels, are assayed from isolated cell types in a group of individuals and studied in the context of a phenotype or condition of interest (e.g., 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…P-values were calculated using the paired t-test for unequal variance after performing Levene's Test. I miR-142-3p expression in FACS-sorted hematopoietic cell populations (n = 5 per group; normalized data were obtained from GEO series GSE98791 [14]). HSC, haematopoietic stem cells; Ery, erythrocytes; Mega, megakaryocytes; Gran, granulocytes; Mono, monocytes; NK, natural killer cells; CD4T = CD4+ T-cells, CD8T = CD8+ T-cells.…”
mentioning
confidence: 99%